HUBUNGAN GAYA KEPEMIMPINAN KEPALA DINAS TERHADAP MOTIVASI KERJA PEGAWAI DINAS SOSIAL PROVINSI KALIMANTAN TIMUR - Diyan Wahyudisam (ADMINISTRASI PUBLIK, 2019)
The object of the research are the employees and the staff of Dinas Sosial Kabupaten Kutai Barat. The type of research is quantitative research, this research aims to solve the problem as it has been formulated previously and to find out if the leadership style of head office has a positive effect on employees motivation in Dinas Sosial Provinsi Kalimantan Timur.The results of the first hypotesist which the authors propose that the leadership style of head office has a positive and significant relations with the work motivation of employees in the Dinas Sosial Provinsi Kalimantan Timur, acceptable or unsubstantiated by using product moment analysis obtained the result of the leadership style relations of the head office has a positive and significant relations with employees motivation at the Dinas Sosial Kutai Barat is 0.584.The linear regression analysis that has been described previously obtained simple equation regression Y = 10.641 + 0,440x. That is the leadership style of head office has a positive relations with the motivation of employees in Dinas Sosial Provinsi Kalimantan Timur. If the leadership style has increased then the resulting employees motivation will also increase.